ChemInform Abstract: Base Promoted Direct C4‐Arylation of 4‐Substituted‐pyrazolin‐5‐ones with Diaryliodonium Salts. Issue 36 (September 2015) - Mao, Song; Geng, Xu; Yang, Yang; Qian, Xiaofei; Wu, Shengying; Han, Jianwei; Wang, Limin
Abstract A DMAP‐mediated arylation of pyrazolinones by diaryliodonium triflates at room temperature is presented.